=2x+7+x+3x+1

Simple and best practice solution for =2x+7+x+3x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for =2x+7+x+3x+1 equation:


Simplifying
0 = 2x + 7 + x + 3x + 1

Reorder the terms:
0 = 7 + 1 + 2x + x + 3x

Combine like terms: 7 + 1 = 8
0 = 8 + 2x + x + 3x

Combine like terms: 2x + x = 3x
0 = 8 + 3x + 3x

Combine like terms: 3x + 3x = 6x
0 = 8 + 6x

Solving
0 = 8 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
0 + -6x = 8 + 6x + -6x
Remove the zero:
-6x = 8 + 6x + -6x

Combine like terms: 6x + -6x = 0
-6x = 8 + 0
-6x = 8

Divide each side by '-6'.
x = -1.333333333

Simplifying
x = -1.333333333

See similar equations:

| -6+4+11y=-16 | | 9w+6.3=5.3 | | 2+3w=12+2w | | (3w-6)(3w-6)= | | 4+-2y+-1y=9 | | =6(x+y)+y+3(x+3) | | 2y-8=10y+24 | | 4x=2x-14 | | 500-20x=0 | | -8n=42 | | -3.6h=10.8 | | 7x+20=8x+2 | | =9+2(x+7)+7(y+2) | | =2y+8(y+1)+5(x+5) | | 4e+-3e+-2e=1+-9 | | Y=5x^3-17x^2-12x | | 23+24a=29+23a | | 5s-1-6s^2=0 | | 5a(3a-5)(5a-1)=0 | | -(2f-4)=-4-f+2 | | 3z+5+2z=13+3z | | =3(x+y)+4(y+x) | | 14+3n=8n-3+10x | | 2x^2+12+9x-18-3x-4x=0 | | x+x+1+x+2=-3.75 | | 11+3x-7=6x+-3x | | 9w-18w-18w+36= | | =6+6(x+4)+15y+x | | -1(x+4)+5=4x+1-5x | | 14+4x+6=8x | | -19x+23y=-3 | | 3x+14x+2=19 |

Equations solver categories